Restoration, revitalization or liquidation: strategies of attitude to cultural heritage - Markovskyi, Andrii; Lagutenko, Olga; Марковський, Андрій Ігорович (Romanian Inventors Forum, 2024)
The article focuses on the main problems and socio-cultural and political challenges related to the attitude of the professional community, state bodies and society as a whole to cultural and artistic monuments. The issues of restoration/revitalization/reconstruction or elimination of cultural heritage were largely actualized as a result of the direct military invasion of the Russian invaders on the territory of Ukraine in order to destroy the country, Ukrainian self-identification and us as a separate, independent nation. The paper provides examples of complex discussion aspects in relation to artefacts of architecture and art of different political eras, different ideological orientation, practical significance, material value and the degree of destruction / preservation in the context of the transformation of society's attitude to them and the prospects for future post-war reconstruction. © 2024 Romanian Inventors Forum. All rights reserved.
Keywords: Architectural monument; Art monument; Avant-garde art; Monumental sculpture; Post-war restoration; Reassignment of symbols; Reconstruction